The Effect of Catalyst Loading (Ni-Ce/Al2O3) on Coconut Copra Pyrolysis via Thermogravimetric Analyzer - Balansundram, Vekes; Norazana, Ibrahim; Ruzinah, Isha; Rafiziana, Md Kasmani; Mohd Kamarudin, Abd Hamid; Hasrinah, Hasbullah; Roshafima, Rasit Ali (AIDIC Servizi, 2017)
The aim of this study is to investigate the influence of catalyst weight loading on pyrolysis of coconut copra via thermogravimetric analyser (TGA). The pyrolysis process is conducted up to 700 °C at a heating rate of 10 °C/min in nitrogen (N2) atmosphere flowing at 150 mL/min. The catalyst was successfully prepared via wet impregnation method, with alumina (Al2O3) used as support, while cerium (Ce) and nickel (Ni) act as promoter. The feedstock samples for TGA were prepared accordingly with biomass to catalyst weight loading ratio as follows: CC-1 (1 : 0.05), CC-2 (1 : 0.10), CC-3 (1 : 0.15), CC-4 (1 : 0.20), CC-5 (1 : 0.50), and CC-6 (1 : 1). For comparison, the pyrolysis of coconut copra without catalyst is also determined at the same operating condition and labelled as CC-7 (1 : 0). The TGA-DTG curves shows that, the presences of catalyst significantly affect the degradation rate of volatile matter than lignin degradation. In this study, the CC-3 sample has achieved high mass loss at 83.27 % and also high degradation rate at 0.0107 mg/s. For lignin decomposition, it shows that, CC-1 to CC-6 samples has achieved lignin mass loss percentage below 12.7 %. The non-catalytic sample (CC-7) has exhibited 80.33 % of volatile matter of mass loss and 13.92 % of lignin mass loss. The optimum catalyst loading was observed at 1 : 0.15 (CC-3) that work best to degrade volatile matter at highest mass loss, in which attributes to higher yield of pyrolysis oil.